Penerapan Enterprise Risk Management dalam Meningkatkan Kinerja Keuangan di Perusahaan “XYZ” - Mohamad A’ar Pranatha; Moeljadi Moeljadi; Erna Hernawati (Ekonomi dan Bisnis, 2018)
The research will be discussed about the impact of the implementation of Enterprise Risk Management in improving financial performance in Company "XYZ". This research is done by using Qualitative method. In this study, the analysis of operational activities and the results of identification shows low risk, medium risk and high risk. This research is done by interview, observation and document analysis about the application of Enterprise Risk Management. This study shows that there are 18 risks that arise in the company. With the ERM, the company is more sensitive to the various risks that can occur the company can also provide an assessment of each risk and provide appropriate response and in accordance with the risk rating and can take a policy on decision making appropriate for the sustainability of the company.